2005
DOI: 10.1259/bjr/75926824
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a digital flat-panel versus screen–film, photofluorography and storage-phosphor systems by detection of simulated lung adenocarcinoma lesions using hard copy images

Abstract: The purpose of this study was to compare hard copy images from a flat-panel detector digital radiography system with conventional radiography, photofluorographic radiography and storage phosphor radiography for the detection of simulated lung adenocarcinoma lesions and also for radiation dose. To test the diagnostic performance of these four systems, the authors used 15 types of lung adenocarcinoma phantom according to Noguchi's classification and an anthropomorphic chest phantom. The visual evaluation of tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…Despite added efforts to avoid errors, some errors are inevitable due to the patient's physical stature, facial asymmetry, or inability to adhere to the instructions 37. According to Ono et al,37 anatomical variations might produce different radiographic images.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite added efforts to avoid errors, some errors are inevitable due to the patient's physical stature, facial asymmetry, or inability to adhere to the instructions 37. According to Ono et al,37 anatomical variations might produce different radiographic images.…”
Section: Discussionmentioning
confidence: 99%
“…According to Ono et al,37 anatomical variations might produce different radiographic images. Additionally, Gianni et al38 stated that professionals who would use this radiography for treatment planning should understand those errors and account for these changes to the best of their ability, using their expertise and experience to ensure treatment success.…”
Section: Discussionmentioning
confidence: 99%
“…In digital and analog chest X-ray systems, the radiation dose was extremely low, with averages ranging between 73 and 198 μGy. However, a phantom study that simulated Noguchi’s Type A small adenocarcinoma revealed that the detection rate was very low by digital and analog chest X-ray systems (Ono et al 2005). …”
Section: Discussionmentioning
confidence: 99%
“…O advento das imagens digitais e seu contínuo desenvolvimento realçaram a necessidade de um sistema de informações que integrasse as informações clínicas do paciente com as suas respectivas imagens médicas (BANKMAN, 2000;AZEVEDO-MARQUES et al,2001;BUSHBERG et al, 2012 (FUHRMAN et al, 1988;KEHLER et al, 1989;MORIOKA et al, 1989;NEUFANG et al, 1989;SCHAEFER et al, 1990;FRIEDMANN;NEUFANG;KRUG, 1991;LEHMANN et al, 1991;MACMAHON et al, 1991;SARTONI et al, 1991;BLUME;JOST, 1992) e à utilização de algumas ferramentas do pós-processamento das imagens médicas tais como, o realce de borda e a inversão das imagens radiográficas digitais (MACMAHON et al, 1988;OESTMANN et al, 1988;SHELINE et al,1988;KHEDDACHE et al, 1991;BLUME;JOST, 1992;ONO et al,2005;PROKOP et al, 2003;MAROLF et al, 2008;REESE et al, 2011).…”
Section: Comunicação Armazenamento E Exibiçãounclassified